Improving Conceptual Understanding of Living Organism Classification through Wordwall Digital Media among Slow Learners in an Inclusive Junior High School - Widia Sari; Shely Cathrin (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
This study aimed to improve students’ understanding of the concept of living organism classification through the use of the Wordwall digital learning media in an inclusive junior high school setting, particularly for students identified as slow learners. The study employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, consisting of two cycles: planning, action, observation, and reflection. The participants were 23 seventh-grade students at SMP Negeri 3 Muara Wahau, with specific attention given to one student identified as having slow learning characteristics. Data were collected through observations, tests, and documentation and analyzed using descriptive quantitative and qualitative techniques. The findings indicated improvements in both the learning process and learning outcomes. Teacher activity increased from 71.87% in the first meeting of Cycle I to 90.62% in the second meeting of Cycle II. Student activity also improved from 58.47% to 75.85% over the same period. Learning achievement showed a notable increase, with the average score rising from 63.04 in the preliminary assessment to 78.70 at the end of Cycle II. No students remained in the low-achievement category, while 56.52% reached the high category and 43.48% were classified in the medium category. The results suggest that Wordwall effectively supports conceptual understanding of living organism classification by providing interactive, engaging, and accessible learning experiences. The media was particularly helpful in facilitating participation and conceptual development among students in inclusive classrooms.